Does the combination of exercise and cognitive training improve working memory in older adults? A systematic review and meta-analysis - Yiqing Wu; Ming Zang; Biye Wang; Wei Guo (PeerJ, 2023)
Background Cognitive functioning is dependent on working memory and a decline in working memory is the main cause of cognitive aging. Many studies have suggested that physical exercise or cognitive intervention can effectively improve working memory in the elderly. However, it is still unknown whether a combination of exercise and cognitive training (CECT) is more effective than either intervention alone. The present systematic review and meta-analysis were undertaken to evaluate the effect of CECT on working memory in the elderly. Methods The review was registered in the International Prospective Systematic Review (PROSPERO, CRD42021290138). Systematic searches were conducted on Web of Science, Elsevier Science, PubMed and Google Scholar. The data were extracted according to the PICOS framework. Comprehensive meta-analysis (CMA) software was used to perform the meta-analysis, moderator analysis and publication bias testing. Results The current meta-analysis included 21 randomized controlled trials (RCT). Results showed that CECT had a significantly greater impact on working memory in older adults compared to no intervention groups (SMD = 0.29, 95% CI [0.14–0.44], p < 0.01), with no significant difference between CECT and exercise (SMD = 0.16, 95% CI [−0.04–0.35], p = 0.12) or cognitive intervention alone (SMD = 0.08, 95% CI [−0.13–0.30], p = 0.44). Furthermore, the positive effect of CECT was moderated by intervention frequency and cognitive state. Conclusions The CECT can effectively improve working memory of older adults, but the effect of CECT compared to single intervention needs to be further explored.